Penguatan Karakter Islami Anak Melalui Program Didikan Subuh Rutin Di Masjid Sebagai Wujud Pengabdian Dosen Kepada Masyarakat - Sakinah, Durrah; Purnamasari S, Ayu; Aswati, Fajar; Ihsan, Muhammad; Rahman, Abdul; Sandi, Ari (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2024)
Community service is an implementation of the Tri Dharma of Higher Education which emphasizes the real contribution of academics in addressing the socio-religious needs of society. This activity was carried out through the regular Didikan Subuh program at the mosque in Tarai Bangun Village with the aim of instilling Islamic values, cultivating worship practices from an early age, and strengthening the role of the mosque as a center of non-formal education. The method used was a participatory method with a descriptive qualitative approach, with the subjects of the activity being elementary school children totaling 35–45 participants. The program was implemented throughout September 2024, involving lecturers, students, mosque administrators, and the local community. The activities included the habituation of performing congregational Subuh prayers, tadarus (Qur’an recitation), interactive sermons, memorization of short prayers and verses, the delivery of Islamic exemplary stories, and the practice of daily Islamic manners. The results of the program indicated an increase in children’s enthusiasm with consistent attendance levels. They became more disciplined in performing worship, accustomed to reciting daily prayers, and showed positive behavioral changes both at home and at school. This program also strengthened the role of the mosque as a center for Islamic character development and enhanced synergy between higher education institutions and the community. Although there were challenges such as inconsistent attendance of some participants and limited time for memorization, solutions in the form of small study groups and simple rewards were effective in increasing children’s motivation. Thus, this program proved to be effective in shaping a Qur’anic generation with noble character while also strengthening the harmonious relationship between lecturers, students, mosque administrators, and the community